Relevansi pemikiran spiritual: Menjawab tantangan interaksi dan kesadaran kolektif di era digitalisasi - purnama, silvia gadis (Maliki Interdisciplinary Journal, 2026)
The development of digital technology in the era of globalization has significantly transformed patterns of social interaction, including in Kota Malang. The widespread use of social media platforms such as WhatsApp, Instagram, and TikTok has enabled faster and broader communication. However, this condition also presents challenges, including the decline in interpersonal communication quality, increased individualism, and the spread of misinformation and hate speech, indicating a shift in collective social awareness. This study aims to examine the relevance of spiritual thought as a solution to these challenges. The research employs a qualitative approach through literature review and analysis of social phenomena. The findings reveal that spiritual thought, encompassing inner awareness, moral values, and social responsibility, plays an important role in rebuilding collective awareness and strengthening the quality of social interactions. Therefore, integrating spiritual values into digital society is a strategic effort to foster more harmonious and sustainable social interactions.